Device-to-Device (D2D) communication in Terahertz (THz) frequency band - Tultul, Nafisa Azad; Hossain, Syed Shafquat; Farha, Subrin (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.